Dating is more than just a game. - Tan, Chia Huee. (2008)
This study investigates the general dating preferences of undergraduates based on the assumption that dating extensiveness helps people narrow down their choice and picks a partner. We analyzed the dating behaviors of undergraduates in the two universities in Singapore and highlight any differences between the two. Our purpose is to decide whether the students from these two universities form a potential market for dating businesses.